FORMATION OF PROFESSIONAL IDENTITY OF MEDICAL WORKERS IN THE PUBLIC ADMINISTRATION SYSTEM: CHALLENGES AND PROSPECTS - Shevchenko, Larysa (Public Management and Policy, 2025)
The article is aimed at analyzing the formation of the professional identity of medical workers in the context of public administration, taking into account modern socio-economic and technological challenges, as well as determining the prospects for its development. The paper emphasizes that the professional identity of a medical specialist is formed under the influence of internal personal determinants (value orientations, normative ideas, ethical attitudes and worldview positions), as well as external social and institutional factors, including societal expectations, occupational status, and career prospects in the healthcare system. The article analyzes the internal structure of professional identity, which includes cognitive, affective and behavioral components that determine the idea of the content of the profession, emotional and value attitude to activities and the practical implementation of professional functions. Attention is focused on the fact that in the modern system of personnel training, professional identity does not always act as an independent goal of the educational process, which requires the integration of purposeful mechanisms for its formation into the public administration system. Particular attention is paid to the regulatory and legal support of professional identity through the legislative definition of the status of a medical worker, the establishment of professional standards and the regulation of continuous professional development. The role of electronic systems for accounting for educational activities, a point system of assessment and digital competencies in stabilizing and updating professional identity is considered separately. The strategic aspect of human resources management is highlighted, which includes the stimulation of interprofessional interaction, autonomy and professional responsibility, which contributes to improving the quality of medical services and public confidence in the health care system. It is generalized that the integration of internal, external and regulatory and managerial factors creates a holistic system for the formation of professional identity, which is a key element of the effective functioning of the public health care sector and the sustainable development of human capital in the industry.